Empirical probabilities of (non)optimal healthcare choice conditional on socio-economic status and time consumption - Vuong, Quan- Hoang (Indian Journal of Community Health, 2016)
Background: Patients need healthcare information for making decisions in choosing health service provider, but data sufficiency and quality are major obstacles. Non-optimal decisions are common. The problem persists even with the growing power of the Internet and ICT-based facilities. Asymmetric information exacerbates the economic inequality, worsening community health. Aims & Objectives: The study reports results on existence of empirical relations between such factor as socioeconomic status, consumption of time and outcome of healthcare provider choice by Vietnamese patients. Material & Methods: Cross-section data from a patient community survey spanning >30 hospitals in Hanoi, during 2015 Q4-2016 Q1. Study sample contains 1459 observations. Main method used is baseline category logits regression. Results: Empirical relations among the above factors are confirmed. The rich possess advantages over the poor, with a >63% probability of making an optimal choice. But two groups are not different with respect to wrong choice, with probabilities of making wrong choice for high- and low-SES patients, spending significant time for seeking information, being 13.6% and 15.1% respectively. Conclusion: a) Even for the rich with significant information the chance of choosing right healthcare provider is relatively low, 51%; b) Quality of information or information processing by healthcare consumers shows some problem.